Do structures with sexual contact functions evolve negative static allometries? A case study with the harvestman Leiobunum vittatum (Opiliones Sclerosomatidae). Issue 1 (2nd January 2017) - Kilmer, J.T.; Rodríguez, R.L.
Abstract : Morphological traits vary in their scaling relative to body size. One of the most general scaling patterns has been found for male genitalia: across many animal groups, differences in body size are associated with small differences in genital size (i.e., genitalia exhibit shallow scaling on body size, or negative static allometry). One potential explanation for this pervasive pattern is that genitalia are selected to scale shallowly for reasons related to the contact nature of the functions they perform during copulation. This hypothesis predicts that non-genitalic structures that touch mates during copulation (to stimulate or grasp the mating partner; "contact structures") will also scale shallowly with body size. We tested this prediction by comparing the static allometric slopes of non-genitalic contact and non-contact structures in Leiobunum vittatum harvestmen. We found that contact structures had shallower allometric slopes than non-contact structures, in support of the contact-function hypothesis. However, we also found that the distalmost segments of appendages had lower slopes than non-distal segments, regardless of their sexual function. Because all of L. vittatum 's contact structures are distal, we were unable to isolate the effects of a structure having a contact function from having a distal position. We recommend further tests to tease apart the effects of these variables.